Monitoring Urban Expansion in Urban Abha Using Remote Sensing and Geographic Information Systems (1984 - 2020) - Al Omeir, Saad Abdullah; Alshwesh, Ibrahim Obaid (Journal of natural sciences, life and applied sciences, 2023)
In light of the improvement in economic conditions and development projects in all regions of the Kingdom of Saudi Arabia throughout the study period. This improvement was accompanied by an increase in the size of the population, which results in pressure on urbanization. The problem of the study is the increasing urban expansion in urban Abha at the expense of the various land uses to accommodate the growing population size, Therefore the study aims to monitor and control the urban growth in Abha besides determining its direction. The study was based on the Spatial Analysis Method to monitor urban growth in urban Abha between 1984-2020 using remote sensing (RS) and geographic information systems (GIS) techniques. The three images of the years 1984, 2002 and 2020 were brought from the website of the Authority US Geological Survey (USGS). The first and second images were from Landsat (5) with the TM sensor, while the third image was from Landsat (8) with the OLI sensor. The improvement, correction and processing operations were done using ERDAS IMGINE 2015 and Arc GIS 10.5). The study found that the size of the urban size in these areas had quadrupled in the period (1984-2020) as the urban size increased from (38.3) km 2 in 1984 AD to (179.6) km 2 in 2020 until it became 19% of its total area (945.7 km2). The study also found that the direction of urban Abha growth takes place in a main east-west axis on the King Fahd Road that connects Abha with Khamis Mushait and several sub-axes. The study recommends the need to manage urban growth with appropriate planning according to the geographical nature of the city on the one hand, and bearing in mind the population’s needs and increase on the other hand. The study stresses the importance of cooperating with specialists and researchers to participate in the planning and management of urban growth to overcome problems.